2013
DOI: 10.1063/1.4826920
|View full text |Cite
|
Sign up to set email alerts
|

Understanding inversion layers and band discontinuities in hydrogenated amorphous silicon/crystalline silicon heterojunctions from the temperature dependence of the capacitance

Abstract: International audienceThe temperature dependence of the capacitance of very high efficiency silicon heterojunction solar cells exhibits an anomalously large increase with temperature that cannot be explained under the usual depletion approximation. Based on a full calculation of the capacitance, we show that this large increase of capacitance with temperature of p-type hydrogenated amorphous silicon (a-Si:H)/n-type crystalline silicon (c-Si) heterojunctions occurs when a strong inversion layer at the c-Si surf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
16
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 17 publications
(17 reference statements)
3
16
0
1
Order By: Relevance
“…The small frequency dispersion of C-T curves at low temperatures has also been observed by other authors [24,25], and is related to hole response and collection at the p-side, but we will not go further into these details here. The overall capacitance increase with temperature is very similar to that previously observed on the high efficiency cell from INES [21].…”
Section: Temperature Dependencesupporting
confidence: 87%
See 3 more Smart Citations
“…The small frequency dispersion of C-T curves at low temperatures has also been observed by other authors [24,25], and is related to hole response and collection at the p-side, but we will not go further into these details here. The overall capacitance increase with temperature is very similar to that previously observed on the high efficiency cell from INES [21].…”
Section: Temperature Dependencesupporting
confidence: 87%
“…8 One might argue that strong temperature dependence of physical parameters like the position of the Fermi level in a-Si:H or the valence band offset might be able to reconcile calculated and experimental data. This is not the case and we have shown that even with unreasonable temperature dependences of these parameters the calculated capacitance still exhibits weaker temperature dependence than observed experimentally [21]. This emphasizes the failure of the existing theory of the depletion capacitance that neglects minority carriers in the calculation of the space charge in cSi.…”
Section: Discussionmentioning
confidence: 42%
See 2 more Smart Citations
“…2 In recent years, a-Si:H layers also garnered significant attention, thanks to their excellent crystalline silicon (c-Si) surface passivation properties, even when only a few nm thin. [3][4][5][6][7][8] This property is exploited with remarkable success for passivating-contact fabrication in silicon heterojunction (SHJ) solar cells, [9][10][11][12][13][14][15][16][17][18][19][20][21][22] with reported conversion cell efficiencies as high as 26.3%. 23 For any solar cell technology, an important criterion for ultimate device performance is its stability under prolonged light exposure.…”
mentioning
confidence: 99%